TINGKAT KEPUASAN PASIEN TERHADAP TINDAKAN KEGAWATDARURATAN DI UNIT GAWAT DARURAT - Endang Soelistiyowati; Irine .; Sulvie Surdianto (Poltekkes Kemenkes Surabaya, 2014)
This research is a descriptive research, with a cross-sectional design, which aims to find a picture of patient satisfaction with emergency measures in the ER Bhakti Rahayu Hospital Surabaya. As the population in this study were all patients in the ED Bhakti Rahayu Hospital Surabaya in July, 2013, with a target population of 60 patients with impaired Airway, Breathing, Circulation, loss of consciousness and ECG in the ER Bhakti Rahayu Hospital in July 2013, all used as research subjects. Data were collected using a questionnaire instrument. The results were analyzed descriptively, where it is known that the majority of patients in the ER Bhakti Rahayu Surabaya satisfy with the emergency action and most of the patients stated that the emergency measures in the ER Bhakti Rahayu Surabaya is included balk. So it is advisable to the hospital management to keep attention to all aspects that may affect patient satisfaction. Keywords: Saving Time , Live Saving